DAMPAK PERKEMBANGAN KAWASAN WISATA PANTAI LIANG TERHADAP MASYARAKAT (Studi Deskriptif pada Masyarakat Desa Liang Kecamatan Salahutu Kabupaten Maluku Tengah) - Syamsuddin Syamsuddin (IAIN Ambon, 2019)
ABSTRACT The impact of Tourist development in tourism areas on an area need balancing of environmental and social interactions, this balance can increase the number of visitors to the tourist area and directly increase the income of the area itself. This research has purpose to know about the impact of regional development in Liang beach as a tourism place to local people who live in Liang village, Salahutu District, Central Molluca Regency. The object of this research is the people who stay in Liang village. The technique of Data collection through interviews and observation. The results of the research, the development of Liang beach as a tourism place has impact on people's economic.the income of food vendors are increase, games rental service, billing entrance, rental of tents and billing services WC, well established community social interaction with visitors and the level of environmental pollution on the development of tourist areas in Liang beach. Keywords: The Impact of Tourist Development, Tourism place , Liang beach